Adams Method Prepared Metal Oxide Catalysts for Solar‐Driven Water Splitting. Issue 3 (23rd January 2018) - Browne, Michelle P.; O'Rourke, Christopher; Wells, Nathan; Mills, Andrew
Abstract: The widespread utilisation of solar‐driven water‐splitting devices is hindered by the use of expensive and unstable materials. Herein, we show that highly active earth‐abundant metal oxide oxygen and hydrogen evolution electrocatalysts can be synthesised using the Adams method, in which the metal salts are oxidised in a melt of sodium nitrate. We also demonstrate that such oxides are usually highly crystalline powders with high specific surface areas. Disc electrodes of the Adams method metal oxides, specifically RuO2, Mn2 O3, Co3 O4 and NiO, are prepared using a recently reported mechanical, solvent‐free method, involving pressing a mixture of the metal oxide and a small amount (5 wt %) of PTFE powder. Each electrode is tested as an electrode for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in 1 m NaOH. In the former role, Mn2 O3 appears better than a platinum wire electrode (overpotential at 10 mA cm −2, η 10 =61 mV compared to 70 mV for Pt). In the OER study, although RuO2 is the best electrocatalyst (with η 10 =267 mV), Co3 O4 is also very effective (with η 10 =330 mV). Using Mn2 O3 as the cathode and Co3 O4 as the anode, a silicon solar cell is used to photocleave water into H2 and O2 . Abstract : Good day sunshine : Highly active earth‐abundant metal oxides, prepared by means of the Adams method, were employed in the preparation of oxygen and hydrogen evolution electrodes. Solar‐driven water splitting in alkaline media was achieved using high‐surface‐area Co3 O4 and Mn2 O3 in pressed Pt disc electrodes, with a 100 % electrochemical efficiency for H2 generation and a 6 % overall solar‐to‐hydrogen efficiency for the two electrode device.